REVOLUSI TEKNOLOGI INFORMASI DAN PENGARUHNYA TERHADAP PERKEMBANGAN SIM DAN MANFAATNYA BAGI AUDITOR - ., Djoko Kristianto (Universitas Slamet Riyadi, 2008)
Abstract Revolution information technology in this time, influencing each;every facet life of modern society, have placed computer technology as indivisible shares in its life to water down and quicken completion of task and also improve their performance. Progress and is sophisticated of technology at this communications era bring consequence conducting of date processing process quickly and effisien with possibility present information output. At management information system framework is in fact recognized two direct coresponding concept with decision making, namely SDS, system decision structured with DSS, System Participation auditor support decision in electronic discussion pass e-mail open other dimension in e-mail exploiting in accountancy area, specially in auditor interest development. With information, many public accountant office which have obtained required date in research into to hit accountancy which is medium happened and arising out impact from change in business world. Auditor require to adapt and join in to exploit internet in their interest development Keywords: Revolution Information Technology, System Decision Structured (SDS), Decision Support System (DSS).